Organizational Practices in the Constitution of the Right to Culture and to the City: Understanding the Struggle for the Rights of a Cultural Organization in Goiás City, Brazil (Desenvolvimento em Questão, 2020)
The objective of this paper is to discuss how the organizational practices in the field of culture constitute the development, promotion and access to rights to culture and to the city in Goiás city, Goiás, Brazil. We bring the theories of the field of Studies Based on Practices (SBP) closer to the Law in order to understand the non-institutionalized legal phenomena of the organizational processes. From a multi-sited ethnography carried out in the Historic Center of the city of Goiás, Goiás, a place classified as a World Heritage Site by UNESCO between August 2014 and December 2015, we highlight the processes by which organizational practices, as producers of spaces in cities, constitute Rights when recognizing or neglecting the occupation of the urban space by certain social groups. We emphasize how the analysis of organizational processes can contribute to a debate on Rights from a perspective of legal pluralism from the daily life of cities and highlighting the relevance of understanding the occupations of urban spaces as a way of reconfiguring relations between the State and civil society.
Keywords: Practices of organization. Rights. Cities. Multi-sited Ethnography. Goiás.